School of Engineering Entrepreneurship as a driver of the development of a digital educational ecosystem for transport and logistics - Drozdova Maria; Fursova Elena (E3S Web of Conferences, 2023)
The article substantiates the relevance and practical significance of the transition of the educational system from traditional to fundamentally new forms that integrate into the digital ecosystem, taking into account global trends in digitalization, the provisions of the state strategy of the digital economy, intellectual priorities of sectoral development. The article reflects the conceptual foundations of the development and implementation of an innovative educational model – the School of Engineering Entrepreneurship (SEE) – created by the team of the first engineering transport university of Russia – the St. Petersburg State University of Railways of Emperor Alexander I (PSUREA). The result of a comprehensive analysis of the already implemented stages of the activities of the SEE, the characteristics of the project directions are presented.